A Comparative Study between Presentation, Practice, Productive (PPP) and Artworks Techniques toward the Enhancement of Students' Descriptive Writing Skills - Silalahi, Fransisca Masta (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2018)
The aim of this study is to find out whether there is any significant difference in enhancing students’ descriptive writing skills between students who acquires Presentation, Practice, Production (PPP) and students who acquires Artworks Technique. This is a quantitative study, utilizing comparative design in order to compare different treatments toward students’ enhancement in descriptive writing skills. The researcher compares the result through pre-test and post-test. After analyzing the data, the researcher found out after being treated using two techniques: PPP and Artworks, students’ skills in descriptive writing is achieved. However, the normalized gain score falls in Low criterion. Aside from that, based on the data analysis there is significant difference between two techniques: PPP and Artworks in enhancing students' descriptive writing skills. In addition to that, the students give positive response after being treated. From the response questionnaire, the mean score falls in High criterion. The scope and delimitations of this study evolve around components of two techniques: PPP and Artworks to provide insights toward enhancing students' ability in writing descriptive text. Keywords Presentation Practice Production (PPP), Artworks, Descriptive Writing Skills